Comment préparer les (futurs) enseignants de FLE à parler de la littérature ? Présentation d’un projet didactique - Górecka, Joanna (Neofilolog, 2022)
The aim of the article is to present the theoretical foundations underlying our didactic work, part of the European project DECLAME’FLE, and its objectives. The proposed reflection concerns the possibility of developing reading practices in FL among readers who are learners of French as a foreign language. The chosen approach exploits the concept of so-called literary reading, oriented towards a theoretical-aesthetic analysis of the text. In the school context, this analysis and interpretation is usually done in dialogue with other readers. However, in the case of personal reading, the reader-learner chooses their texts freely and is not supervised in the activity. We argue that media resources can be an effectively used by learners in their reading and in the analytical and reflective tasks that follow. Based on observation categories from discourse analysis and with reference to research on literary reading, we propose exercises for (future) teachers of French as a foreign language. Their aim is to model the reading of journalist and popular critical discourse in order to draw information from it about the book, the author and the presence of the book in the public space, observe the discourse strategies used and integrate them, in order to be able to talk about reading experiences and make presentations of appreciation of texts.